1978
DOI: 10.1021/i160068a002
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decomposition of Hydrogen Sulfide

Abstract: The decomposition of hydrogen sulfide on molybdenum disulfide and tungsten disulfide catalyst was studied at 500-800 °C. It has been found that molybdenum disulfide catalyst decomposes hydrogen sulfide effectively into hydrogen and elementary sulfur over the whole range of temperature employed in this study, and that it is possible to convert more than 95 % of the hydrogen sulfide fed to the reaction system into hydrogen and sulfur by continuous removal of sulfur and Intermittent separation of hydrogen from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(63 citation statements)
references
References 7 publications
1
60
0
2
Order By: Relevance
“…In the presence of nickel an increase in signal intensity after CO adsorption is observed already at 295 K while the unpromoted sample has to be heated to 473 K. In this respect it is noteworthy that especially nickel sulfide and cobalt sulfide have a high activity for the formation of COS (17). These findings suggest that CO adsorption may very well occur on a sulfur ion belonging to the coordination sphere of both a tungsten ion and a decorating nickel ion in case of Ni(4)-W(19.3)/Si02.…”
Section: Injuence Of Co Adsorption Upon the Esr Spectramentioning
confidence: 97%
See 1 more Smart Citation
“…In the presence of nickel an increase in signal intensity after CO adsorption is observed already at 295 K while the unpromoted sample has to be heated to 473 K. In this respect it is noteworthy that especially nickel sulfide and cobalt sulfide have a high activity for the formation of COS (17). These findings suggest that CO adsorption may very well occur on a sulfur ion belonging to the coordination sphere of both a tungsten ion and a decorating nickel ion in case of Ni(4)-W(19.3)/Si02.…”
Section: Injuence Of Co Adsorption Upon the Esr Spectramentioning
confidence: 97%
“…Another possibility is the formation of COS, a reaction that is known to take place over transi- tion metal sulfides (17). This reaction would lead to the donation of electrons:…”
Section: Injuence Of Co Adsorption Upon the Esr Spectramentioning
confidence: 99%
“…In recent years, many researchers have studied the feasibility of producing hydrogen by enhancing the conversion of dehydrogenation/decomposition reactions. Dokiya et al (1977), Fukuda et al (1978), and Kameyama et al (1981) employed porous Vycor glass to selectively separate the hydrogen produced in the decomposition of hydrogen sulfide. In a separate study using the same reaction, Kameyama et al (1983) showed the possibility of using porous alumina membranes.…”
Section: Background Studymentioning
confidence: 99%
“…Various studies have been carried out previously, pertaining to non-catalytic [7] and catalytic decomposition * corresponding author; e-mail: hfigen@yildiz.edu.tr of H 2 S, employing metal oxides [1] and metal suldes [3,4,8,9]. Perovskites (ABO 3 ) catalysts are known to be more stable, and their activity can be improved depending on element B [10].…”
Section: Introductionmentioning
confidence: 99%